Frontiers in Atmospheric Pressure Plasma Technology - Nastuta, Andrei Vasile (2022)
Atmospheric pressure plasma discharges have grown rapidly in importance in recent decades, due to the ease in handling and operation, plus their eco-friendly applications, for agriculture, food, medicine, materials and even the automotive and aerospace industries. In this context, the need for a collection of results based on plasma technologies is justified. Moreover, at the international level, the increased number of projects that translated to publications and patents in the multidisciplinary field of plasma-based technology gives researchers the opportunity to challenge their knowledge and contribute to a new era of green services and products that society demands. Therefore, this book, based on the Special Issue of "Frontiers in Atmospheric Pressure Plasma Technology" in the "Applied Physics" section of the journal Applied Sciences, provides results on some plasma-based methods and technologies for novel and possible future applications of plasmas in life sciences, biomedicine, agriculture, and the automotive industry.This book, entitled "Frontiers in Atmospheric Pressure Plasma Technology", consists of 8 research articles, 2 review articles and 1 editorial. We know that we are only managing to address a small part of what plasma discharge can be used for, but we hope that the readers will enjoy this book and, therefore, be inspired with new ideas for future research in the field of plasma.